Sebaran Aktivitas Radionuklida Alam dalam Sedimen di Perairan Sluke Rembang, Jawa Tengah - Jarot Marwoto; Muslim Muslim; Zanet Dwi Aprilia; Purwanto Purwanto; Murdahayu Makmur (Universitas Diponegoro, 2019)
The existence of natural radionuclides has been around since the earth was formed. Steam Power Plant in Sluke Rembang is operated by coal fuel that produces some natural radionuclides that release as a gas through the chimney to atmosphere. These radionuclides fall on the land and sea. The purpose of this study was to know the activity of gamma-emitting natural radionuclides in sediments and its distribution in the Sluke waters of Rembang. The result showed that activity of 40K, 212Pb, 226Ra dan 228Ac appeared fluctuating with a range from 160.54-503.87 Bq/kg; 88.62-333.34 Bq/kg; 66.07-95.24 Bq/kg and 95.30-466.46 Bq/kg respectively. The distribution of natural radionuclides was affected by topography, resources and the movement patterns of currents that move from the source of radionuclides to the northeast. The data obtained in this study will serve as baseline data in natural radionuclide in Sluke, Rembang. Keberadaan radionuklida alam sudah ada sejak bumi terbentuk. Pusat Listrik Tenaga Uap (PLTU) di Sluke Rembang dioperasikan dengan bahan bakar batu bara yang menghasilkan beberapa radionuklida alam dalam bentuk gas yang dilepaskan melalui cerobong asap ke atmosfir. Radionuklida tersebut akhirnya jatuh di darat dan di perairan laut. Penelitian ini bertujuan untuk mengetahui aktivitas radionuklida alam dalam sedimen dan distribusinya di perairan Sluke, Rembang. Hasil penelitian menunjukkan nilai aktivitas radionuklida alam 40K, 212Pb, 226Ra dan 228Ac berfluktuasi, secara berturut-turut adalah dari 160,54-503,87 Bq/kg; 88,62-333,34 Bq/kg; 66,07-95,24 Bq/kg dan 95,30-466,46 Bq/kg. Distribusi aktivitasnya dipengaruhi oleh topografi, sumber dan pergerakan pola arus yang bergerak dari sumber radionuklida menuju ke timur laut. Hasil penelitian ini dapat digunakan sebagai baseline unsur radionuklida alam (NORM) di Sluke Rembang.